Presence of Achatina fulica in the Triple Border – Paraguayan side – a parasitological screening - Meza Ocampos, Griselda; Nakayama, Héctor; Segovia Corrales, Edith Alba; Llano, Ismael (Archives of Veterinary Science, 2025)
Achatina fulica, (sinom. Lissachatina fulica) or commonly the African Giant Snail (AGS) appears among these exotic species invaders, originating from the East of Africa, and was introduced voluntarily or accidentally in more than 50 countries, which had a negative impact on biodiversity, ecosystems, agriculture and public health. This study aimed to confirm the presence of Achatina fulica in Paraguay and analyze feces, slime and lung tissue in the search of eggs, cysts and larvae of parasites. Fifty specimens were captured in the city of Presidente Franco, Paraguay. The presence of parasites was evaluated using routine parasitology techniques. The average weight was 21.61 grams and 6.26 cm in length. 93% (46/50) of the specimens had parasite eggs, larvae and cysts in fecal samples. No eggs or larvae were found in slime. In the analysis of the lung tissue, eggs and larvae of Strongylid type and Ascaris type was observed. AGS represents a potential threat to the biodiversity of the area and is considered as carrier of parasites. More studies at the molecular level of the larvae recovered are expected to be carried out in the future.